2019
DOI: 10.1016/j.csr.2019.06.004
|View full text |Cite
|
Sign up to set email alerts
|

A methodology based on data filtering to identify reference fleets to account for the abundance of fish species: Application to the Striped red mullet (Mullus surmulletus) in the Bay of Biscay

Abstract: For data-limited stocks (DLS), professional fishing data can be used as a potential source of information, especially in the absence of appropriate scientific survey, to understand abundance evolution under realistic hypothesis on resource catchability. This work focuses on a data-filtering approach, the selected fishing effort must reflect vessel activity that is least dependent on their technical characteristics and as stable as possible over time. The variable of interest is landing by fishing sequence (lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…They can be found around the first 100 m (Mahé et al, 2005), although large surmullets were observed at more than 300 m (Caill-Milly et al, 2017).We therefore assumed a depth range of 0-300 m for the group. Detailed vertical distribution can be found in Section S3, Table S6.…”
Section: Mulletsmentioning
confidence: 99%
“…They can be found around the first 100 m (Mahé et al, 2005), although large surmullets were observed at more than 300 m (Caill-Milly et al, 2017).We therefore assumed a depth range of 0-300 m for the group. Detailed vertical distribution can be found in Section S3, Table S6.…”
Section: Mulletsmentioning
confidence: 99%